Post-soviet legacies and conflicting values in Europe : generation whY? - Surzhko-Harned, Lena; Turkina, Ekaterina (Russian, Eurasian, and Eastern European politics., 2018)
This book explores generational conflict in Europe through the prism of politico-economic and institutional values. It finds a dramatic shift of values in post-Soviet societies, where post-Soviet Generation WhY stands apart from previous generations. The book investigates the details and the implications of this phenomenon.